(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
Contemporary advertising has become an essential means of social, economic, and cultural communication. In the context of the rapid development of media and digital technologies, advertising texts occupy an important place in everyday life and exert a significant influence on consumers’ behavior, opinions, and choices. The linguo-pragmatic study of French advertising texts makes it possible to analyze not only their linguistic characteristics but also the pragmatic mechanisms employed to attract the attention of the target audience and produce a persuasive effect. This research focuses on the analysis of discursive strategies, stylistic devices, and expressive means used in modern French advertising.